2023
DOI: 10.1039/d3sm00291h
|View full text |Cite
|
Sign up to set email alerts
|

Design and characterization of molecular, crystal and interfacial structures of PVDF-based dielectric nanocomposites for electric energy storage

Abstract: PVDF-based polymers with polar covalent bonds are next-generation dielectric materials for electric energy storage applications. Several types of PVDF-based polymers, such as homopolymer, copolymers, terpolymers and tetrapolymers, were synthesized by...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 172 publications
0
2
0
Order By: Relevance
“…Methods such as the selection of PVDF copolymers, solution casting of pristine PVDF, and incorporation of nanofillers have proven successful in promoting the electroactive (β and γ) phases of PVDF. [24][25][26] Interestingly, PVDF films that exhibit the γ phase and possess a dense microstructure have been observed to perform well in energy storage applications compared to other variations, underscoring the influence of phase and structure on the material's performance. [27][28][29] Song et al demonstrated higher performance in LFP cells with an increased β phase.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Methods such as the selection of PVDF copolymers, solution casting of pristine PVDF, and incorporation of nanofillers have proven successful in promoting the electroactive (β and γ) phases of PVDF. [24][25][26] Interestingly, PVDF films that exhibit the γ phase and possess a dense microstructure have been observed to perform well in energy storage applications compared to other variations, underscoring the influence of phase and structure on the material's performance. [27][28][29] Song et al demonstrated higher performance in LFP cells with an increased β phase.…”
Section: Introductionmentioning
confidence: 99%
“…The electroactive β‐phase of PVDF has been reported to be induced by electrical poling and stretching of the polymer at high temperatures. Methods such as the selection of PVDF copolymers, solution casting of pristine PVDF, and incorporation of nanofillers have proven successful in promoting the electroactive (β and γ) phases of PVDF [24–26] …”
Section: Introductionmentioning
confidence: 99%